PENGARUH SEDUHAN DAUN ALPUKAT TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Sumirat, widhi (Jurnal AKP, 2013)
Currently shifting diet of community from traditional food menu which rich in fiber and nutrient to fast food which high fat content, salt, and calorie but poor in fiber and nutrients. Salt and saturated fat nutrients in fast food increase the risk of hypertension. Hypertension impact is earning happened stroke, heart attack, kidney disturbance, and eyes disturbance. One treatment deribved from herbs, which uses avocado leaves. Patient of hypertension in the community do not know the majority of the benefits of avocado leaves as lowering blood pressure. This research is to know influence of steep of avocado leaves to blood preasure to patient of hypertension Research Desain which is used in this research is " Experiment pre", One- Group- Pre- Post Test- Desaign with technique intake non random sampling . With population a number of 28 responder and sempel a number of 12 responder that is one who suffer hypertension with age 40-60 year which do not medium experience medication. Data collected by using observation sheet. Data analysis is conducted by calculateng mean manually.From result of research is got that most responder is degradation of blood pressure from mean of pretest 144,16/93,33 becoming 134,58/86,66.From description of above can be concluded that happened degradation blood pressure respondednt is given steep of avocado leaves 1 times one day in range of time 7 day successively. So that steep of avocado can degrade blood pressure to patient of hypertension. Keywords: Patient, Hypertension, steep of Avocado leaves.